Invasive cystic hypersecretory carcinoma of the breast - Srilata Chitti,; Sunayana Misra,; Arvind Ahuja,; Nikhil Gupta,; Raghav Yelamanchi, (Autopsy and Case Reports, 2022)
Cystic hypersecretory carcinoma (CHC) of the breast is a rare variant of ductal carcinoma, characterized by variably sized cysts lined by micropapillary fronds to proliferative pseudostratified columnar epithelium. It includes a spectrum of morphological features ranging from clearly benign cystic hypersecretory hyperplasia (CHH), CHH with atypia to invasive CHC. Only 20 cases of invasive CHC have been reported to date. We report a case of a 49-year-old female who presented with a palpable breast lump and nipple discharge. Gross examination showed variable-sized cysts lined by solid grey white tumors. On microscopic examination, cysts were lined by micropapillary fronds with eosinophilic colloid-like secretion with a focus of invasion. A diagnosis of invasive CHC was made. Since there are limited case reports, our understanding of its biological behavior, prognostic factors, and genetic basis is limited.